Principles and practices to integrate livestock into Ethiopia's rainwater management systems - Haileslassie, Amare (International Livestock Research Institute, 2011)
During the 2011 Third International Forum on Water and Food (in South Africa) Amare Haileselassie from ILRI reflected on ways that livestock can be integrated into rainwater management systems and strategies in Ethiopia. The overall aim is to improve 'livestock water productivity' through the adoption of various practices at farm and landscape levels.